Effects of trace alloying elements on the phase transformation behaviors of ordered ω phases in high Nb-TiAl alloys. (5th January 2017) - Song, Lin; Lin, Junpin; Li, Jinshan
Abstract: Ordered ω phases are equilibrium phases at intermediate temperatures in TiAl alloys. However, a systematical research on the effects of alloying elements on the ordered ω phase transformations is still lacking. The effects of alloying elements on the ordered ω phase formation should be considered in future design of TiAl alloys. In this study, the effects of Cr, Mn and Ni on the ordered ω phase formation are investigated. The results show that the precipitation of ordered ω phase is promoted by addition of Ni, i.e., the sizes of ordered ω phase were in micron-level. However, the addition of Mn greatly suppresses the growth of ordered ω phases. During thermal exposure at 850 °C, a Ti-Al-Ni ternary phase formed within the original βo phase areas in the Ni-containing alloy. Meanwhile, no ordered ω phase existed in an annealed Mn-containing alloy. In both as-cast and annealed conditions, the effects of Cr seemed to be similar to those reported in Mo and W-containing alloys. Differential scanning calorimetry (DSC) experiments suggested that the precipitation temperatures of ordered ω phase in these three alloys were affected by minor alloying elements, which fitted well with the observed phenomena in the electron microscopy study. Graphical abstract: Highlights: The effects of Cr, Mn and Ni on the formation of ordered ω phases were studied. Mn suppressed the formation of ordered ω phases. ωo and βo phases co-existed in the Cr-containing alloy after annealing. A Ti-Al-Ni ternary phase was identified in Ni-containing TiAl alloy after annealing.